Black carrot extract protects against hepatic injury through epigenetic modifications. Issue 10 (28th June 2022) - Kitano, Atsuko; Norikura, Toshio; Matsui‐Yuasa, Isao; Shimakawa, Hiromi; Kamezawa, Makoto; Kojima‐Yuasa, Akiko
Abstract: We studied the epigenetic regulation of how black carrot extract (BCE) protects against ethanol‐induced hepatic damage. We have shown that the butanol‐extracted fraction of BCE (BCE‐BuOH) increased intracellular cyclic adenosine monophosphate (cAMP) levels by suppressing the expression of phosphodiesterase 4b (PDE4b); however, the detailed mechanism remains to be elucidated. We focused on changes in histone modifications involved in the suppression of pde4 expression. The methylation level of histone H3 lysine 9 (H3K9), which regulates gene expression of PDE4b, decreased after treatment with 100 mM ethanol but was significantly increased by treatment with 400 μg/ml BCE‐BuOH. In contrast, ethanol induced an increase in H3K9 acetylation. However, treatment with BCE‐BuOH inhibited the increase in acetylation through an increase in Sirtuin 1 (Sirt1), a histone deacetylase. Furthermore, BCE‐BuOH treatment increased the level of methionine adenosyltransferase (MAT) 2a mRNA and increased intracellular S‐adenosylmethionine. The present results indicate that BCE‐BuOH is useful for protection against alcohol‐induced hepatic injury. Practical applications: We have reported that black carrot extract (BCE) suppressed liver steatosis and liver fibrosis on a rat alcoholic liver disease model. The results from this study have shown that BCE regulated the alcoholic‐induced hepatic injury at the level of epigenetic modifications. These results suggested that BCE is useful for protection against alcoholic‐induced hepatic injury. Abstract : BCE‐BuOH protects against ethanol‐induced hepatic injury through epigenetic modifications. The methylation level of histone H3K9, which regulates gene expression of PDE4b, decreased after treatment with 100 mM ethanol but was significantly increased by treatment with BCE‐BuOH. On the other hand, alcohol induces an increase in the acetylation of H3K9, which regulates the gene expression of pde4b. Treatment with BCE‐BuOH inhibited the increase in acetylation through an increase in Sirt1, a histone deacetylase. Furthermore, BCE‐BuOH treatment increased the level of Mat2A mRNA and then increased intracellular SAM.